IMPLEMENTASI METODE SAW (SIMPLE ADDITIVE WEIGHTING) SEBAGAI PENDUKUNG KEPUTUSAN UNTUK REKOMENDASI HABITAT KELINCI BERBASIS IoT (INTERNET OF THINGS) - Anderias Eko Wijaya; Nur Imam Iskandar (Jurnal Teknologi Informasi dan Komunikasi, 2020)
Rabbits are mammals from the family Leporidae (green plant eaters) which can be found in many parts of the earth. Rabbits are very susceptible to temperature changes. Temperature greatly affects the rabbit's body metabolism. The temperature ideal for rabbits is in the range of 60 – 650F or equal to 15.5 - 18.30C temperature is known as "comfort zone" for rabbits. The level of heat stress in rabbits is very high in the tropics thereby reducing rabbit productivity. With a system that researchers can make it easier to determine the suitable place to serve as a rabbit habitat with the Internet of Things system network, and reduce the failure rate in keeping rabbits as well as the implementation of the node-ed as a platform to display the results of the calculation method of the decision. The system is applied using the SAW (Simple Additive Weight) ranking method or commonly called this weighted method by using three parameters including temperature; humidity; light. However, the data must go through a calculation that generates a value of each location then normalize to get a decision by the sum of the multiplication of normalization with weights. Implementation Methods of SAW (Simple Additive weighting) as Decision Support Habitat For Rabbits Recommendation Based IoT (Internet Of Things) has been successfully applied. So that it can rank rabbit habitat locations based on parameters of temperature, humidity, light. However, although the system is built based on IOT but has not publicly accessible or still based on the localhost.